Identification of Genes Subject to Positive Selection in Uropathogenic Strains of Escherichia coli: A Comparative Genomics Approach - Chen, Swaine L.; Hung, Chia-Seui; Xu, Jian; Reigstad, Christopher S.; Magrini, Vincent; Sabo, Aniko; Blasiar, Darin; Bieri, Tamberlyn; Meyer, Rekha R.; Ozersky, Philip; Armstrong, Jon R.; Fulton, Robert S.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2006)
Escherichia coli is a model laboratory bacterium, a species that is widely distributed in the environment, as well as a mutualist and pathogen in its human hosts. As such, E. coli represents an attractive organism to study how environment impacts microbial genome structure and function. Uropathogenic E. coli (UPEC) must adapt to life in several microbial communities in the human body, and has a complex life cycle in the bladder when it causes acute or recurrent urinary tract infection (UTI). Several studies designed to identify virulence factors have focused on genes that are uniquely represented in UPEC strains, whereas the role of genes that are common to all E. coli has received much less attention. Here we describe the complete 5,065,741-bp genome sequence of a UPEC strain recovered from a patient with an acute bladder infection and compare it with six other finished E. coli genome sequences. We searched 3,470 ortholog sets for genes that are under positive selection only in UPEC strains. Our maximum likelihood-based analysis yielded 29 genes involved in various aspects of cell surface structure, DNA metabolism, nutrient acquisition, and UTI. These results were validated by resequencing a subset of the 29 genes in a panel of 50 urinary, periurethral, and rectal E. coli isolates from patients with UTI. These studies outline a computational approach that may be broadly applicable for studying strain-specific adaptation and pathogenesis in other bacteria.